2019
DOI: 10.1002/mrd.23166
|View full text |Cite
|
Sign up to set email alerts
|

Changes in calcium levels in the endometrium throughout pregnancy and the role of calcium on endometrial gene expression at the time of conceptus implantation in pigs

Abstract: Calcium plays an essential role in regulating many cellular functions, including proliferation, differentiation, and apoptosis. In spite of its importance in the establishment and maintenance of pregnancy, changes in calcium levels at the maternal–conceptus interface during pregnancy and its action on endometrial gene expression are not well understood. Thus, we examined changes in calcium levels in the endometrium during pregnancy, calcium deposition at the maternal–conceptus interface during pregnancy, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Studies in both pigs and sheep indicate that calcium and phosphate increase in uterine flushings during the peri-implantation period of pregnancy, and are more abundant in uterine flushings from pregnant than cyclic animals during the mid-luteal phase of the estrous cycle [ 18 , 19 , 27 , 28 ]. Further, temporal changes in the abundance of minerals in the uterine lumen during the peri-implantation period are accompanied with striking alterations in the expression of molecules with regulatory roles in phosphate, calcium, and vitamin D transport and signaling [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both pigs and sheep indicate that calcium and phosphate increase in uterine flushings during the peri-implantation period of pregnancy, and are more abundant in uterine flushings from pregnant than cyclic animals during the mid-luteal phase of the estrous cycle [ 18 , 19 , 27 , 28 ]. Further, temporal changes in the abundance of minerals in the uterine lumen during the peri-implantation period are accompanied with striking alterations in the expression of molecules with regulatory roles in phosphate, calcium, and vitamin D transport and signaling [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium ions are key regulators for both embryo implantation and microvilli formation, and they can provide a greater surface area on the apical side of the cells; thus allowing asymmetric localization of membrane transporters, cytoskeletal proteins, and enzymes on EECs, eventually enhancing cell polarity [35]. Previous studies have revealed that blocking endometrial calcium channels can cause complete implantation failure in mice during the implantation window stage [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mRNA expression of proliferation-related PCNA in the EEC in the HS treatment group was remarkably lower than that in the control group (Figure 7C). MUC1 and ZO-1 have been reported to be related to embryo implantation and cell adhesion [35,36]. The cultured porcine endometrial epithelial cells exposed to heat stress at 42 • C for 0 h were used as a control to obtain the relative mRNA expression of MUC1 and ZO-1.…”
Section: Effects Of Heat Stress On Porcine Endometrial Epithelial Cellsmentioning
confidence: 99%
“…During implantation, the trophoblast cells in the blastocyst create tissue and physiological connections with the endometrial epithelium, which stabilize the development of the blastocyst in the uterus [ 7 , 8 ]. The critical phase in pigs is day 12 of gestation (gd12), whereby the embryonic morphology changes dramatically from tubular to filamentous, accompanied by the secretion of large amounts of estrogen and interleukins; estrogen levels peak on gd12 and can be harnessed to validate pregnancy to facilitate embryo implantation [ 9 , 10 , 11 ]. Given that the porcine embryo floats in the uterine luminal fluid (ULF) before implantation, the ULF serves as a necessary route of maternal–fetal interaction, and extracellular vesicles (EVs) in the ULF participate in information transmission [ 12 ].…”
Section: Introductionmentioning
confidence: 99%